A Perspective of Foreign Debt – A Case Study of Indonesia - Selvia Inca Devi (Proceedings of AICS - Social Sciences, 2017)
This study aims to analyze the effect of Gross Domestic Product (GDP), government expenditure, and budget deficit partially and simultaneously to foreign debt in Indonesia. The type of data in this study is secondary data in the form of time series from 2000 to 2014 obtained from Bank Indonesia and Badan Pusat Statistik. The method of analysis used in this study is multiple linear regression analysis, t-test, f-test and coefficient of determination. The partial test results show that Gross Domestic Product (GDP), and budget deficit have a positive effect and significant on foreign debt in Indonesia, while government expenditure has a negative effect and significant on foreign debt in Indonesia. There is a significant influence of Gross Domestic Product (GDP), government expenditure, and budget deficit to foreign debt in Indonesia with 91.8%